0165 Prevalence of insomnia and/or obstructive sleep apnea in a sample of fit-for-duty U.S. Navy sailors. (25th May 2022) - Lawrence-Sidebottom, Darian; Matsangas, Panagiotis; Shattuck, Nita
Abstract: Introduction: Obstructive sleep apnea (OSA) and insomnia are prevalent sleep disorders, known to negatively impact sleep and well-being in civilian populations. Studies of these sleep disorders in military populations have focused on individuals seeking treatment for a sleep disorder, rather than the general active-duty service member (ADSM). In this study, we investigated the prevalence of OSA and insomnia in U.S. Navy sailors serving on surface ships. Methods: We analyzed pre-collected data from 548 fit-for-duty sailors (MD age=25 years, IQR=9; 79.4% males) serving on nine US Navy surface ships. Sailors reported their demographic information, health-related habits, and whether they had been diagnosed with OSA and/or insomnia. Sleep was assessed with wrist-worn actigraphy (371 sailors). Results: Approximately 66.8% of sailors reported having an exercise routine, 83.6% reported drinking caffeinated beverages, and 29.1% used nicotine products. In terms of disorders, 15 (2.7%) male sailors reported having been diagnosed with OSA, 12 (2.2%) with insomnia (8 males, 4 females), and one (0.2%) male sailor with comorbid insomnia and OSA. Compared to sailors without a sleep disorder, sailors with OSA were older (MD=34 years, IQR=7; p<0.001) and had a higher proportion of nicotine users (53.3%) (p=0.041). Sailors with insomnia did not differ from sailors with no sleep disorder in terms of demographics and habits. The average daily sleep duration was 6.4±1.0 hours, which did not differ between disorder groups. However, sailors with insomnia had more sleep episodes per day (MD=1.7; IQR=0.9) than sailors without a sleep disorder (MD=1.3, IQR=0.5; p=0.042). Conclusion: Only 5% of the sailors in our study reported a diagnosis of OSA and/or insomnia, whereas one in three people in the general population has a sleep disorder. Notably, all sailors, regardless of sleep disorder diagnosis, exhibited short sleep durations. Previous studies of ADSMs found that 48% reported poor enough sleep quality to meet the diagnostic criteria for a sleep disorder. Thus, our results suggest that, despite evidence that many Sailors exhibited sleep problems, sleep disorders are significantly underdiagnosed in ADSMs. Support (If Any): This work was supported in part by the Naval Medical Research Center's Naval Advanced Medical Development Program (MIPR N3239820WXHN007).